High purity hydrogen production via aqueous phase reforming of xylose over small Pt nanoparticles on a γ-Al2O3 support. (18th May 2020) - Kim, Yoondo; Kim, Minkyeong; Jeong, Hyangsoo; Kim, Yongmin; Choi, Sun Hee; Ham, Hyung Chul; Lee, Seung Woo; Kim, Jin Young; Song, Kwang Ho; Yoon, Chang Won; Jo, Young Suk; Sohn, Hyuntae
Abstract: In this study, aqueous phase reforming (APR) of xylose was conducted over highly dispersed Pt nanoparticles supported on a γ-Al2 O3 support (Pt-SNP). Formation of small Pt nanoparticles was confirmed by X-ray diffraction and transmission electron microscopy, which revealed that most of the particles ranged between 0.8 and 1.6 nm in size and the average particle size was 1.3 nm. Temperature-programmed reduction analysis indicated that these small Pt nanoparticles were highly reducible under the reducing environment compared to the commercial Pt/γ-Al2 O3 catalysts (Pt-commercial). The catalytic activities of both Pt-SNP and Pt-commercial catalysts were examined in a semi-batch autoclave reactor system for the APR of xylose. It was found that Pt-SNP showed higher carbon to gas conversion with high hydrogen selectivity than Pt-commercial. This was likely due to the increased density of edge sites in the Pt-SNP catalyst that facilitated the cleavage of the C–C bonds rather than the C–O bonds, leading to greater hydrogen production. Furthermore, the Pt-SNP catalyst showed better carbon deposit resistance as compared to Pt-commercial. The amount of carbon deposition on the Pt-SNP catalyst surface and the organic carbon species dissolved in the post-reaction xylose solution were significantly lower compared to that of Pt-commercial. Finally, high purity hydrogen production was achieved using a continuous fixed-bed hybrid reactor including an aqueous phase reformer and a home-made Pd/Ta dense metallic composite membrane. A stable hydrogen gas production (99.999%) was obtained over the Pt-SNP catalyst, which demonstrated the success of a potentially commercial APR reactor system that continuously converted the aqueous xylose solution to hydrogen with high purity. Graphical abstract: Image 1 Highlights: Pt/γ-Al2 O3 catalysts with Pt particle size of 1.3 nm (av.) was synthesized (Pt-SNP). High hydrogen selectivity was obtained over Pt-SNP for APR of xylose. Increased density of edge sites improves C–C bond cleavage during APR of xylose. High purity hydrogen was achieved using a continuous fixed-bed hybrid reactor. This hybrid reactor includes an APR reformer and a Pd/Ta composite membrane.